Isoform profile of NOS enzyme in structure of rats' solitary-vagal complex in arterial hypertension of various origin - M. V. Danukalo; O. V. Hancheva (Zaporozhye State Medical University, 2020)
The aim of this study was to characterize the nitric oxide isoforms profile in rats' nucleus tractus solitarii (NTS) and dorsal motor nucleus (DMN) of vagus nerve in arterial hypertension (AH) of various origin (essential (EAH) - rats of SHR line, and endocrine-salt AH). Materials and methods. The study was performed on 30 aged male rats. Among them, 20 Wistar rats were divided into two groups - control (10 rats) and 10 rats with simulated endocrine-salt AH (ESAH) and 10 SHR rats. An immunohistochemical method was used to study the of nitric oxide synthase isoforms expression features in DMN and NTS. The following parameters were determined: the content of immunoreactive material (IRM) for the studied peptides (Uif), the relative area of the IRM (%) and the IRM concentration in 1 μm2 (Uif/μm2). Results. It was found that in rats with both models of AH, the expression indices of all three nitric oxide synthase (NOS) isoforms in the studied structures increased. In our opinion, this is due to the activation of the studied structures in AH conditions. This must be considered as an important element of high blood pressure compensating. It is achieved through the implementation by a complex of mechanisms like reducing of the sympathetic tone and increasing of the parasympathetic tone by activating a system of secondary messengers; improving neurotrophy due to the high activity of constitutive NOS isoforms; iNOS-mediated NO overproduction, as a factor in compensating for its bioavailability in conditions of local ischemia in AH. Conclusions. Regardless of the AH etiopathogenesis in both experimental groups, the expression of all three NOS isoforms increases in the DMN and NTS structures. In rats with EAH in the DMN and NTS structures, the expression indices of NOS isoforms have their own characteristics. So in the first structure, the largest changes in the indices of the immunoreactive material content and concentration are observed for eNOS, and the relative area for iNOS. At the same time, in the NTS structure, the largest changes in the content indices are observed for iNOS, and the concentration and relative area for eNOS. In rats with ESAH in the DMN structure, the highest changes in the indices of IRM content and concentration are observed for the endothelial isoform of NOS, and the relative area - for inducible. In the NTS structure, the IRM content changed the most for nNOS, and the concentration and relative area for iNOS.